Lose the clutter, lose the weight eaudiobook The six-week total-life slim down. - Walsh, Peter (Tantor Media, 2015)
A houseful of clutter may not be the only reason people pack on extra pounds, but research proves that it plays a big role. A recent study showed that people with supercluttered homes were 77 percent more likely to be overweight or obese! In Lose the Clutter, Lose the Weight , organizing guru Peter Walsh comes to the rescue with a simple 6-week plan to help listeners: — Clear their homes of excess "stuff" as they discover their vision for their personal space — Clear their bodies of excess pounds as they follow a healthy, supersimple eating and exercise plan — Clear their minds and spirits of the excess weight of too many possessions Rodale took the program for a testdrive with two dozen volunteers who followed his plan. All reported great results—from significant weight loss to calmer minds and more organized, happier, and more efficient lives.